Measurement of the inclusive isolated prompt photon cross section in pp collisions at s=1.96 TeV using the CDF detector - Aaltonen, T; Adelman, J; Alvarez Gonzalez, B; Amerio, S; Amidei, D; Anastassov, A; Annovi, A; Antos, J; Apollinari, G; Apresyan, A; Arisawa, T; Artikov, A; et al. (2009)
A measurement of the cross section for the inclusive production of isolated photons by the CDF experiment at the Fermilab Tevatron collider is presented. The measurement covers the pseudorapidity region |ηγ|<1.0 and the transverse energy range ETγ>30GeV and is based on 2.5fb-1 of integrated luminosity. The sample is almost a factor of 7 larger than those used for recent published results and extends the ETγ coverage by 100 GeV. The result agrees with next-to-leading order perturbative QCD calculations within uncertainties over the range 50